Creation of passivated Nb/N p-n co-doped ZnO nanoparticles and their enhanced photocatalytic performance under visible light illumination. Issue 4 (April 2019) - Gao, Shuang; Yang, Weiyi; Xiao, Jun; Li, Bo; Li, Qi
Abstract: Passivated niobium/nitrogen (Nb-N) p-n co-doped zinc oxide nanoparticles were created by a simple precipitation process with in-situ self-formed NaCl "cage" to confine the nanoparticle growth followed by the heat treatment in a flow of ammonia gas. Enhanced optical absorbance into the visible light region was observed in the Nb/N co-doped ZnO nanoparticle photocatalyst due to the Nb/N co-doping effect. It demonstrated a largely enhanced photocatalytic performance in the disinfection of Escherichia coli bacteria under visible light illumination, which could be attributed to the passivated co-doping of Nb-N to suppress the photogenerated charge carrier recombination on dopants. This robust approach for passivated p-n co-doping may also be applied to other material systems for a wide range of technical applications.